Algae Removal from Petrochemical Industry Wastewater Using Biocide: Factorial Analysis - N., Zainol; N. S., Hasbullah (2018)
The petrochemical industries have high potential in the creation of environmental impact. The water from industry is mostly containing toxic pollution [1]. Lagoon system is one of the most popular methods for wastewater treatment. Lagoons are in-ground earthen basins used for the treatment of industrial wastewater by natural process involving the use of algae and bacteria [2]. However, excessive algae growth can cause algae blooms. In wastewater treatment, algae blooms are one of major problem that can cause high pH value in the wastewater plant. There are dozens of alternatives for algae removal such as sand filtrations, chlorination and others. Thus, biocide was used in this study to remove algae in petrochemical wastewater. By using biocide, it has the advantage of producing a high quality effluent for a reasonable operating and maintenance costs. Four independent factors such as type of biocide, ratio of biocide and synthetic wastewater volume (B/W), agitation rate, and hydraulic retention time (HRT) were investigated. A two level factorial design was used to investigate the effect of the independent factors as well as the interaction factors on the pH and reduction of algae mass (%). The experiment was conducted by adding certain amount of salt into certain amount of synthetic wastewater. Shake flask method was applied to study the reaction. The initial and final mass of algae was determined by using dry weight measurement method. The reduction of algae was calculated in Equation 1.